Building trust in clinical research: a systems approach to ethical engagement and sustainable outcomes - Blom, Johanna M. C.; Rivi, Veronica; Tascedda, Fabio; Pani, Luca (Frontiers in Pharmacology, 2025)
Trust and trustworthiness are critical to the success of clinical research, profoundly influencing participant engagement, data integrity, and study outcomes. These behaviors emerge from complex, dynamic interactions within the clinical research ecosystem, involving stakeholders such as sponsors, participants, clinicians, researchers, and regulatory bodies. The rapid development of COVID-19 vaccines has underscored the potential of scientific advancements to build public trust in the scientific outcomes, while also exposing vulnerabilities in the procedural trust framework due to misinformation and historical unethical practices. This paper explores trust and trustworthiness as emergent properties within the complex systems of clinical research, highlighting their evolution through transparent communication, participant empowerment, and ethical governance. A systems approach is emphasized, where trust develops holistically, influenced by regulatory frameworks, interpersonal relationships, and the overall research environment. Practical implications include the adoption of adaptive consent models, interdisciplinary collaboration, and the integration of continuous feedback mechanisms. To address trust erosion, especially among marginalized communities, we advocate for participatory research approaches and the development of new professional competencies, such as the role of a Clinical Research Liaison. This role would ensure ongoing alignment with community needs, enhance transparency, and maintain ethical standards, ultimately fostering a research environment where trust and trustworthiness thrive, benefiting both participants and the broader scientific community. A roadmap for future efforts includes the systematic incorporation of these elements into clinical research practices to enhance trust and improve research outcomes.